The ferroelectric PLZT type ceramics as a material for transducers - Czerwiec, Marek; Zachariasz, Radosław; Ilczuk, Jan (Archives of Acoustics, 2007)
Modification of the PZT system by the addition La^3+ ions has marked beneficial effect on several the basic parameters, such as squerness of the hysteresis loop, decreased coercive filed, increased dielectric constant, maximum coupling coefficients, increased mechanical compliance, and enhanced optical transparency. The mechanical and electrical properties in lanthanum modified lead zirconate-titanate ceramics of 5/50/50 and 10/50/50 were studied by electric permittivity ε and dielectric losses tan δ measurements. The temperature dependences of ε = f(T) and tan δ = f(T) were determinate in temperature range from 300 K to 730 K. The values of T_C obtained during ε and tan δ measurements were respectively: 560 K for 5/50/50 and 419 K for 10/50/50.